Makna Kekerasan bagi Perempuan Korban Kekerasan dalam Rumah Tangga di Pekanbaru - Sari, Genny Gustina; Surya, Santhiana (Jurnal Studi Komunikasi, 2018)
The violence that happens in the household every year is always increasing. This incident is more and more revealed because of the law that regulates the abolition of violence in the household. The Indonesian people still consider that domestic violence is limited to physical violence, but in the abolition of domestic violence there are four types of violence, namely; 1) physical violence, 2) psychic violence, 3) sexual violence and, 4) economic violence. The purpose of this study is to know how the physical and psychological meaning of women victims of domestic violence and to know the communication experience of women victims of violence in the household. This research uses qualitative research method with phenomenology approach. The study subjects consisted of three women victims of family sergeant who were obtained by using snowball technique. Data collection techniques in this study through in-depth interviews, and documentation, to achieve the validity of data in this study, the authors use the extension of participation, and triangulation. The results showed that physical violence performed in the form of slap, pulled hair, and kicks, while psychic violence obtained, cursing, demeaning, and pressure. The communication experiences of women victims of domestic violence tend to be negative or unpleasant in the form of being threatened, insulted and degraded by the husband and become the gossip material of the neighbor.